The advancement of eduction in agriculture - Wilson, George Helen (My University, 1905)
Introduction: Agriculture, originally the tillage of the soil, is now applied in a broader sense to the practical scientific business of the farm, in all its details of tillage, crops, stock -raising and labor, The term "practically scientific" implies the application of the laws and principles of the exact sciences to the practice of the art of Agriculture. practical skill to be really successful must be guided by science which is simply the experience of many men concisely arranged and systematized There is always in a farming family an amount of useful information handed down from father to son which proves of much practical value. Notwithstanding this fact it is very essential that the farmer have a knowledge of all the sciences relating to Agriculture; such as horticulture, entomology, geology, zoology, soil physics, and chemistry, Agriculture, considered in its crude state is one of the oldest of human occupations, dating from before the dawn of history. The savage who lived by the fruits and roots he found ranked lower in the scale than the hunter who lived by the chase. The herdsmen, although leading a wandering life, belonged to a higher grade of the human race than the hunter, but civilization in the true sense only began when men had settled habitations and tilled the soil for their sustenance. The inhabitants of Switzerland are the oldest Agriculturists and stock-raisers known to us. Domestic animals were raised by these people centuries ago, and wheat, barley, millet, and flax seem to have been cultivated at an early age in the world's history, but old as it is, agriculture has only reached its present stage of development in recent years, and there are some wild tribes which have very crude methods and some who neither plow nor sow. Egypt and Babylonia were among the great agricultural communities of the ancient world and the leading principles of Agriculture were earnestly practiced by the Romans.
Citation: Wilson, George Helen. The advancement of eduction in agriculture. Senior thesis, Kansas State Agricultural College, 1905.
Morse Department of Special Collections
Keywords: Form and Constitution of Shorthorn; Commercial Fertilizers; Agricultural College and Experiment Station; Theses